Meningkatkan Kepercayaan Diri Anak Menggunakan Metode Look and Do - Fajar Utama Ritonga; Manda Veronica (Yayasan Literasi Sains Indonesia, 2023)
Childhood is an essential period in human life. Because it is during this period that childrens have strong memories so that they can easily learn and develop from what childrends see and hear. Every human, who is going through growth and development, through various phase and stage in life. From infants, babies, toddlers, children, teenagers and adults. Crucial moments in growth and development lies on the stages of children and teenagers. In the stages of adolescence and adulthood, every child must be equipped. Debriefing children can be done in various ways and methods of learning. Before entering the public environment with peoples, every children must be equipped with a sense of self-confidence to make it easier for children to socialize with the surrounding environment. In hence to achieve,the needs of self-development of children at the Ora Et Labora Nusantara Orphanage, located at Jalan Perkutut No. 44, Central Helvetia, Kec. Medan Helvetia, Medan City, North Sumatra, learning activities are carried out with a system of mutual participation and interaction in each activity. The learning method is called the Look and Do Method. The goal is that every child is able to express himself so that in the development towards adolescence to adulthood each child is equipped with a sense of self-confidence.